Uterine Epithelial Cells Specifically Induce Interferon-Stimulated Genes in Response to Polyinosinic-Polycytidylic Acid Independently of Estradiol - Patel, Mickey V.; Ghosh, Mimi; Fahey, John V.; Wira, Charles R. (PloS one, 2012)
Interferon β (IFNβ) is an antiviral cytokine secreted in response to pathogenic exposure that creates a restrictive intracellular environment through the action of downstream interferon-stimulated genes (ISG). The objective of this study was to examine the expression of IFNβ and ISG in both human uterine epithelial cells (UEC) and the ECC-1 uterine epithelial cell line and determine if expression changes with TLR stimulation and hormone exposure. Stimulation of primary uterine epithelial cells and ECC-1 cells with the TLR3 agonist poly (I:C) induced the mRNA expression of IFNβ, MxA, OAS2 and PKR. Other TLR agonists including imiquimod and CpG had no effect on either IFNβ or ISG expression. In contrast to ECC-1 cell responses which were slower, maximal IFNβ upregulation in UEC occurred 3 hours post-stimulation and preceded the ISG response which peaked approximately 12 hours after poly (I:C) exposure. Unexpectedly, estradiol, either alone or prior to treatment with poly (I:C), had no effect on IFNβ or ISG expression. Blockade of the IFN receptor abrogated the upregulation of MxA, OAS2 and PKR. Furthermore, neutralizing antibodies against IFNβ partially inhibited the upregulation of all three ISG. Estradiol, directly and in the presence of poly (I:C) had no effect on IFNβ and ISG expression. These results indicate that uterine epithelial cells are important sentinels of the innate immune system and demonstrate that uterine epithelial cells are capable of mounting a rapid IFN-mediated antiviral response that is independent of estradiol and is therefore potentially sustained throughout the menstrual cycle to aid in the defense of the uterus against potential pathogens.